EVALUASI KESESUAIAN LAHAN SECARA FISIK UNTUK TANAMAN KEDELAI DI KELURAHAN PANDU KECAMATAN MAPANGET KOTA MANADO - Orpa Frasawi; Maria Montolalu; Meldi Sinolungan; Rafli Kawulusan (COCOS, 2014)
ABSTRACTThis study aimed to know physical land suitability for soybean crops in the Pandu Village, Mapanget District of Manado. This research can provide input and information to the government and the people of the district of Mapanget about land suitability, especially for soybean plants, which were held at Pandu Village, Mapanget District of Manado city, and at the Laboratory of Soil Conservation and Physics, Faculty of Agriculture of Unsrat for 6 ( six ) months, commencing from March to August 2013, by using the method of Land Survey Unit Approach. The results showed that, the agricultural land at Pandu Village has some potential areas for development of soybean plants. Area I and VI were categorized into suitability classes S2 ( quite appropriate ), Area II was the suitability class S3 ( marginally suitable ), Area III was suitability class N1 ( not appropriate at this time ), Area IV were conformity classes N2 ( not appropriate forever )Keyword: Physical Land Suitability, Soybean